PSYCHOLOGICAL DYNAMICS OF WOMEN WITH THE FIRST PREGNANCY WORKING IN WANDER: PSYCHOLOGICAL DYNAMICS OF WOMEN - Wisnu Catur Bayu Pati; Sri Yuliatin; Dian Mardi Yani (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2022)
Background: Pregnancy is one of the important phases that will be later by women in general. The presence of prospective children also brings up feelings of happiness especially if always accompanied by family. However different things happen when pregnant women have to work and wander. The goal of the study was to understand the psychological dynamics in women with first pregnancies and work in wander. Methods: This study used qualitative methods with phenomenological approaches. Participants in this study were 2 women with the first pregnancy who worked in wander. The data collection techniques used are in-depth observations and interviews. Result:. This study produced 7 major themes including: 1) Physical and psychological conditions when positively pregnant; 2) Problems during pregnancy; 3) Work environment; 4). Relationships with family; 5) Relationship with husband; 6) Coping during pregnancy; 7) Hope during pregnancy and welcome the birth of the first child. Conclusion:Psychologically pregnant women feel anxiety, worry and stress. Physically there are changes from easily tired, nausea, changes in body shape and sleep disorders appear. Socially, there has been no significant change.